Strengthening Religious Moderation Among the People of Madura through Religious Mentoring Activities Based on Local Wisdom - Hadi, Saiful (JURNAL ISLAM NUSANTARA, 2024)
This study explores efforts to enhance religious moderation among the Madurese community through local wisdom-based religious mentoring. The concept of wisdom here encompasses social religion, social culture, and social economy. The research focuses on strengthening Madurese community moderatism through such mentoring activities. Conducted as a field study with qualitative methods, this research relies on primary data from observations and interviews, and secondary data from statistical and literature sources. Using the Miles and Huberman analysis technique, the study yields two key findings. Firstly, the current state of religious moderation in Madurese society is unhealthy, evidenced by the rise of religious groups or movements exhibiting conservatism and radical tendencies in addressing contemporary social religious issues. Secondly, the Madurese community possesses local wisdom values that support religious moderation, including pesantren institutions, traditional cultural constructions with high respect for religious symbols, and diverse resources significantly influencing collective religious awareness. Efforts to strengthen religious moderation involve local wisdom-based diversity assistance activities, utilizing community worldviews that reflect their creativity and unique social religious characteristics. This study's results can significantly contribute to enhancing religious moderation in Indonesia, serving as a reference for other regions with similar characteristics. The findings can help develop a religious mentoring model that leverages local wisdom and measures its effectiveness in fostering moderate attitudes and behaviors.